Geography and the Inclusive Economy: A Regional Perspective - Megan Claridge (New Zealand Government, The Treasury, 2001)
The paper expands on the regional geographic dimensions of the inclusive economy outlined in Treasury Working Paper 01/15 Towards an Inclusive Economy. It discusses the extent to which differences in economic and social indicators across regions might constitute problems, illustrates the importance of understanding empirical patterns of deprivation in New Zealand and outlines some key policy directions. In some instances, differences in indicators of well-being between regions indicate positive dynamics, for example cities generate higher productivity and wages as well as consumption benefits. In other instances, regional differences may be problematic, for example when spillovers perpetuate social problems or people become stuck in declining areas. Auckland is important - it contains 36% of all deprived neighbourhoods in New Zealand, and the proportion is growing over time. Rural deprived regions, particularly Northland and Gisborne with 24% of their population living in deprived neighbourhoods, also warrant attention if people are stuck or community functioning is impaired. There is a high preponderance of Maori and Pacific peoples in both urban and rural deprived neighbourhoods. Avenues for policy exploration include education, enhancing connectedness, and ensuring that people are free to move to job-rich areas. Intervention in local economies needs to be selective and evaluation of all policy intervention is important. Policies that are spatially neutral may have unintended spatial effects and this also requires further attention.
Keywords: R10; 330; economic geography; spatial distribution; deprivation; regions; regional policy